Acute Epididymo-orchitis–Related Global Testicular Infarction: Clinical and Ultrasound Findings With an Emphasis on the Juxta-epididymal String-of-Bead Sign. Issue 3 (September 2016) - Chang, Ching-Di; Lin, Jui-Wei; Lee, Chen-Chang; Chen, Yen-Ta; Huang, Chung-Cheng; Lee, Yi-Wei; Ng, Shu-Hang; Ko, Sheung-Fat
Abstract : Abstract: Acute epididymo-orchitis (AEO)–related global testicular infarction (GTI) is rare. We report herein the clinical and ultrasound findings of 6 patients with AEO-related GTI. Seventeen patients with torsion-related GTI were also reviewed and compared. The echotexture of AEO-related GTI ranged from mildly inhomogeneous to diffuse heteroechoic, depending on the severity of testicular necrotic changes. All of the patients showed a juxta-epididymal string-of-bead pattern on color Doppler ultrasound, which was ascribed to patent arteries (5/6, 87%) and collateral vessels (1/6, 13%) in the tunica albuginea. There were no significant differences in age, laterality, leukocyte count, testicular volume ratio (infarcted/normal), frequencies of heteroechoic testicular parenchyma, scrotal skin thickening, and hydrocele between the 2 groups. However, the left testis was predominantly affected in both groups. Compared with torsion-related GTI, patients with AEO-related GTI had significantly longer duration from scrotal pain onset to surgery (13.5 ± 5.2 vs 2.6 ± 2.0 days, P < 0.001), a higher level of serum C-reactive protein (110.0 ± 82.0 vs 41.2 ± 35.9 mg/dL, P = 0.013), a higher frequency of the juxta-epididymal string-of-bead sign (100% vs 12%, P < 0.001), and a lower frequency of the whirlpool/knot sign (0% vs 88%, P = 0.002). Although the testis in AEO-related GTI may appear variable from mildly to extensively heteroechoic on gray-scale ultrasound, this unusual disease can be characterized by an avascular testis with a juxta-epididymal string-of-bead sign on color Doppler ultrasound.